Matrixing Designs for Shelf-Life Determination of Parenteral Drug Product: A Comparative Analysis of Full and Reduced Stability Testing Design - Lara Pavčnik; Igor Locatelli; Tina Trdan Lušin; Robert Roškar (MDPI AG, 2024)
This article highlights the applicability of matrixing designs in stability studies for parenteral medications. The traditional approach involves extensive testing over the product's shelf-life. However, matrixing designs offer an alternative approach where only a fraction of samples is tested at each time point. The study conducted in this article focused on three parenteral medications and examined stability data under long-term condition. Degradation products were identified as critical parameter, and kinetics of degradation varied among the selected products. A systematic methodology was adopted to evaluate the data using different matrixing designs. The regression models obtained were assessed using statistical parameters S and R2. Also, each of the 28 matrixing designs were compared to the full design with statistical parameter RMSE and the shelf-life. The results confirmed that each of the evaluated matrixing designs can be applied, whether degradation product shows a linear or non-linear increase, and demonstrated that a reduction of two time points per batch is the most appropriate. In conclusion, this research contributes to the understanding of utilizing reduced matrixing designs in stability studies for parenteral medications and can be an effective strategy to reduce costs and time of stability testing while maintaining the necessary level of precision and reliability.